The relationship between organizational justice and empowerment and their impact on achieving organizational commitment (field study in the Department of Labor and Vocational Training) - سعد, هديل كاظم (Journal of Economics and Administrative Sciences, 2011)
The research has deal with the relationship between organizational justice and empowerment and their impact on the achievement of organizational commitment in the office of Labour and Vocational Training. To study the research problem which is represented a sense that employees with low levels of organizational justice and empowerment and the reflection on the organizational commitment of the employees, so that Has been collecting data and information relating to research by designing a questionnaire, were distributed to a sample of (50) people in the office mentioned, and the results of the study to confirm the research hypotheses. and the key results of the research was the presence of correlation relationships and the effect of the research variables, either the most important proposals was the need for the attention of officials in the organization discussed in the achievement levels of organizational justice associated with the empowerment of employees and which are reflected on the organizational commitment